2014
DOI: 10.2478/v10222-012-0089-x
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinesterase Activities of Selected Polyphenols – a Short Report

Abstract: In this work, anticholinesterase activities of 24 polyphenolic compounds were tested using the modified Ellman's spectrophotometric method. The most efficient acetyl-and butyrylcholinesterase inhibitors were anthocyanins (pelargonidin, delphinidin and cyanidin), flavones (apigenin and luteolin), flavonols (quercetin, kaempferol and myricetin), as well as dihydrochalcone phloridzin and prenylated chalcone xanthohumol. It was established that all the tested compounds were within a narrow molecular weight range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 36 publications
3
44
0
Order By: Relevance
“…Phenolic compounds were chosen for testing, based on previous studies [2,6,18]. The results obtained in the current study confirm the in vitro anticholinesterase activity of these compounds.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Phenolic compounds were chosen for testing, based on previous studies [2,6,18]. The results obtained in the current study confirm the in vitro anticholinesterase activity of these compounds.…”
Section: Discussionsupporting
confidence: 73%
“…Anthocyanins pelargonidin (PEL), delphinidin (DEL) and cyanidin (CYA), flavones apigenin and luteolin, flavonols quercetin (QUE), kaempferol (KAE) and myricetin (MYR), dihydrochalcone phloridzin (PHL) and prenylated chalcone xanthohumol are the most efficient in vitro inhibitors of AChE and/or BChE in a study testing 24 polyphenols. The lowest inhibitory activity is exerted by flavan-3-ols [6]. Flavonoids inhibit the formation and extension of amyloid-β (1 -40) or (1 -42) fibrils (in decreasing order: MYR = morin = QUE > KAE > (+)-catechin = (-)-epicatechin [7].…”
Section: Introductionmentioning
confidence: 99%
“…Many plant derived phytochemicals claimed for nootropic activity have shown AChE inhibitory effect and/or antioxidant activity [59]. To our knowledge, based on thorough literature search, there was no report on AChE inhibitory effect of Abelmoschus esculentus .…”
Section: Discussionmentioning
confidence: 99%
“…Carbamate pesticides show their toxicity by irreversibly modifying the catalytic serine residue of AChE, and the inhibiting the AChE 67 . Recently, several studies supported that many active compounds from plant origins, including anthocyanins and terpenoids have AChE inhibition activity 68,69 . Additionally, some studies demonstrated that grape and blueberry anthocyanin 70,71 , grape skin anthocyanin 72 lycodine-type alkaloids from Lycopodiastrum casuarinoides 73 have neuroprotective roles.…”
Section: Introductionmentioning
confidence: 99%